Locus of Control, Self Efficacy, and Time Budget Pressure in Audit Judgment: The Moderating Role of Task Complexity - Erlangga Prakasa; Koeswayo, Poppy Sofia; Mubarrok, Ahmad Zakie (EQUITY, 2025)
This research uses task complexity as a moderating variable to empirically evaluate the effects of locus of control, self-efficacy, and time budget pressure on audit judgment. This study collected answer from auditors who worked for KAP in Bali.   The collected data was analyzed using IBM SPSS Statistics in order to assess validity, reliability, and hypotheses. The results of the research show that locus of control, self-efficacy, and time budget pressure have a significant impact on audit judgment.   The results of the moderation test show that task complexity affects the link between audit judgment and time budget pressure, but it has no effect on the relationship between self-efficacy and locus of control. Keywords: Time Budget Pressure; Audit Judgment; Self Efficacy; Locus Of Control; Task Complexity.